Light-Controlled Friction by Carboxylic Azobenzene Molecular Self-Assembly Layers - Xue, Dandan; Ma, Liran; Tian, Yu; Zeng, Qingdao; Tu, Bin; Luo, Wendi; Wen, Shizhu; Luo, Jianbin (Frontiers in Chemistry, 2021)
Nowadays, reversible friction regulation has become the focus to scientists, flexible regulatory structure of photosensitive materials and theories facilitates rapid development of this field. Meanwhile, as an external stimulus, light possess great potential and advantages in spatiotemporal control and remote triggering. In this work, we demonstrated two photo-isomerized organic molecular layers, tetra-carboxylic azobenzene (NN4A) and dicarboxylic azobenzene (NN2A), which were selected to construct template networks on the surface of the highly oriented pyrolytic graphite (HOPG) to study the friction properties, corresponded to the arrangement structure of self-assembled layers under light regulation. First of all, the morphology of the self-assembled layer was characterized by scanning tunneling microscope (STM), then the nanotribological properties of the template networks were measured by atomic force microscope (AFM). Their friction coefficients are respectively changed by about 0.6 and 2.3 times under light control. The density functional theory (DFT) method was used to calculate the relationship between the force intensity and the friction characteristics of the self-assembled systems under the light regulation. Herein, the use of light external stimulus plays a significant role in regulating the friction properties of the interface of the nanometer, hopefully serving as a fundamental basis for further light-controlling research for the future fabrication of advanced on-surface devices.